2017
DOI: 10.5194/cp-13-1751-2017
|View full text |Cite
|
Sign up to set email alerts
|

Multi-century cool- and warm-season rainfall reconstructions for Australia's major climatic regions

Abstract: Abstract. Australian seasonal rainfall is strongly affected by large-scale ocean-atmosphere climate influences. In this study, we exploit the links between these precipitation influences, regional rainfall variations, and palaeoclimate proxies in the region to reconstruct Australian regional rainfall between four and eight centuries into the past. We use an extensive network of palaeoclimate records from the Southern Hemisphere to reconstruct cool (April-September) and warm (October-March) season rainfall in e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 65 publications
0
71
0
Order By: Relevance
“…Similarly, it was found that megadroughts exceeding 5‐years duration occurred in eastern Australia numerous times during the last millennium, including a 39‐year long drought during an unprecedented century of aridity (Vance et al, ). Similarly, the rate of recent declines in cool season rainfall in parts of southern Australia has been unusual though not unprecedented in the context of the last 400 years, while the spatial extent and duration of the Millennium Drought appears unprecedented over this multi‐century reconstruction period (Freund et al, ). These droughts challenge existing water storage strategies.…”
Section: The Significance Of Recent Regional Rainfall Trends and Theimentioning
confidence: 99%
“…Similarly, it was found that megadroughts exceeding 5‐years duration occurred in eastern Australia numerous times during the last millennium, including a 39‐year long drought during an unprecedented century of aridity (Vance et al, ). Similarly, the rate of recent declines in cool season rainfall in parts of southern Australia has been unusual though not unprecedented in the context of the last 400 years, while the spatial extent and duration of the Millennium Drought appears unprecedented over this multi‐century reconstruction period (Freund et al, ). These droughts challenge existing water storage strategies.…”
Section: The Significance Of Recent Regional Rainfall Trends and Theimentioning
confidence: 99%
“…The hydroclimatic conditions are also extraordinary in the longer term. Freund et al (2017), for instance, showed that the extent and severity of the Millennium Drought (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) were unprecedented over the past 400 yr, and that the 2010-2011 period (Fig. 2B) was amongst the wettest summer periods in the past several centuries.…”
Section: Discussionmentioning
confidence: 99%
“…Drier areas (500-1000 mm yr -1 ), typically in rain shadows and at lower elevations, support dry open eucalyptus forests and woodlands, which have fire return intervals of 10-50 yr (Cheal, 2010). The timing of debris flows across the full study area was examined in relation to regional hydroclimate and wildfire data between 2003 and 2013, when climate fluctuations were large (van Dijk et al, 2013;Freund et al, 2017).…”
Section: Study Area: Dissected Uplands Of Southeast Austrliamentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider finer scale or local hydroclimatic patterns in relation to large-scale climate drivers of a region so that more spatially focussed regional assessments of drought and flood variability and hence water availability can be made (Freund et al, 2017). This also applies when considering the effect of catchment development along a river (Kingsford and Thomas, 2001).…”
Section: Introductionmentioning
confidence: 99%